Knowledge Complementarity of a Firm's Internal and External R&D Capabilities - Heli Koski; Rauli Svento (The Research Institute of the Finnish Economy (ETLA), 2014)
We use data from over 1500 Finnish companies for the years 2006-2008 and 2008-2010 to explore complementarity of a firm's R&D strategy with its external knowledge acquisition and innovation collaboration strategies. We define knowledge complementarity (tacit knowledge complementarity) of R&D capabilities to exist when increase in investments in R&D also increases marginal returns from broader external knowledge search (deeper innovation collaboration with external partners). Our estimation results provide support for knowledge complementarity of external R&D. Instead, our data provide no evidence on tacit knowledge complementary of external R&D generally. However, our empirical results concerning the separate types of external R&D suggest that a firm's acquisition of new technology (i.e., advanced machinery, equipment or software) for innovation purposes appears to be tacit knowledge complementary.
Keywords: D83; O3; L2; 330; open innovation; external knowledge search; complementarity